PREFERENSI KONSUMEN TERHADAP “PRIVATE LABEL” RITEL MODERN DIKAITKAN DENGAN KARAKTERISTIK KONSUMEN: STUDI KASUS PADA PRODUK GULA DI LOTTE MART BANDUNG - Elly Rasmikayati; Siti Tari Syamsiah; Agriani Hermita Sadeli; Bobby Rachmat Saefudin (Universitas Galuh Ciamis, 2021)
PT Lotte Mart Shopping Indonesia Bandung, as one of the modern retailers in Bandung, has a number of products with private label, including sugar products. This study aims to analyze the relationship between consumer characteristics and consumer preferences for